2015
DOI: 10.1097/dcr.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Management of Squamous-Cell Carcinoma of the Rectum

Abstract: This series demonstrates that good results can be obtained by using a rectum-conserving strategy. Close follow-up should be maintained, with the use of salvage surgery reserved only for persistent disease or relapse (see Video, Supplemental Digital Content 1, http://links.lww.com/DCR/A155).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 22 publications
3
19
1
1
Order By: Relevance
“…Surgical resection is a consideration , but increasing numbers of recent studies are also finding merit to treat with definitive CRT using the anal SCC paradigm . Along with the data herein, several series have shown high clinical response as well as clinical complete response rates from 63% to 100% along with 5‐year overall survival, disease‐free survival, and disease‐specific survival rates of 81%, 72%, and 88%, respectively .…”
Section: Discussionmentioning
confidence: 60%
“…Surgical resection is a consideration , but increasing numbers of recent studies are also finding merit to treat with definitive CRT using the anal SCC paradigm . Along with the data herein, several series have shown high clinical response as well as clinical complete response rates from 63% to 100% along with 5‐year overall survival, disease‐free survival, and disease‐specific survival rates of 81%, 72%, and 88%, respectively .…”
Section: Discussionmentioning
confidence: 60%
“…Overall, rectal SCC has a worse prognosis than adenocarcinoma and features associated with poor prognosis are ulcerated or annular carcinomas, node-positivity, and advanced stages (8). While many consider surgical resection the gold standard, some believe that chemotherapy with or without radiation may be curative, and some believe in neoadjuvant chemoradiation prior to tumor resection (9)(10)(11)(12)(13). It is best to individualize treatment based on patient functional status, concurrent comorbidities, tumor staging and local invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these modalities has been tried individually and in conjunction with others in combination treatment with different temporal relationships [12]. Success has been documented with almost all possible combinations of above modalities [12][13][14][15][16][17]. Surgery was traditionally used in concordance with treating anal canal SCC.…”
Section: Discussionmentioning
confidence: 99%
“…There has also been similar shift in preference towards definitive chemo-radiation for Rectal SCC [15,16,18,19]. A systematic review comparing chemo-radiation with traditional surgical approach demonstrated an overall survival of 86% in the chemoradiation group vs. 48% in surgery group.…”
Section: Discussionmentioning
confidence: 99%